Tailoring electrospun Poly(L-lactic acid) nanofibers as substrates for microfluidic applications - Pimentel, E. S. (2020)
Novel microfluidic substrates based on electrospun poly(l-lactic acid) (PLLA) membranes were developed to increase the limited range of commercially available paper substrates, commonly used for the fabrication of microfluidic paper-based analytical devices. PLLA’s advantageous properties include biodegradability, biocompatibility, ease of being processed in various tailored morphologies, and cost effectiveness, among others. Oriented and nonoriented electrospun PLLA membranes were fabricated using electrospinning and the influence of fiber orientation, addition of hydrophilic additives, and plasma treatments on the morphology, physicochemical properties, and capillary flow rates were evaluated and compared with the commercial Whatman paper. In addition, a proof-of-concept application based on the colorimetric detection of glucose in printed PLLA and paper-based microfluidic systems was also performed. The results show the potential of PLLA substrates for the fabrication of portable, disposable, eco-friendly, and cost-effective microfluidic systems with controllable properties that can be tailored according to specific biotechnological application requirements, being a suitable alternative to conventional paper-based substrates.